Hubungan Pekerjaan Ibu Dengan Kejadian Persalinan Preterm Dengan Ketuban Pecah Dini di RSUD Dr. Rasidin Padang Dan RSIA Siti Rahmah - Antari, Gladeva Yugi; Afrida, Baiq Ricca (Universitas Qamarul Huda Badaruddin, 2018)
Background, preterm labor increases infant mortality significantly, where the incidence of preterm delivery ranges from 5% to 18% of all deliveries. The WHO present 2013, Indonesia was ranked fifth out of 10 countries with the highest number of preterm birth in the world with amounted to 675.700 preterm births. Preterm labor caused by many factors, 50% occurred spontaneously, divided into 30% due to premature rupture of membranes (PROM) and 20% were born on indications of maternal/fetal. Factors of preterm labor increase in condition such as genetic, infection, nutrition, behavior and the environment. But in many cases of preterm labor, the emergence of early labor triggers occurs subclinically such as a work.The purpose of this study was the association between mother works with preterm labor with premature rupture of membranes .The study design was comparative cross-sectional at Dr. Rasidin Padang hospital and Siti Rahmah hospital in September to July 2016. Samples in this study are 40 inpartu preterm were selected by consecutive sampling, samples were divided with preterm inpartu with preterm rupture of membranes and preterm inpartu without premature rupture of membranes. this study show is no significant association between the work of mothers with preterm delivery of SPD and preterm not KPD. The conclusion of this study that the value of p = 1 obtained a value of p> 0.05, it can be concluded that there is no significant relationship between maternal work between preterm KPD delivery and not KPD.